Canonical analysis of climatic factors associated with the quality characteristics of drinking water of a city in São Paulo State - Rodrigues, Sérgio Augusto [UNESP]; de Oliveira, Paulo André; Cervi, Ricardo Ghantous [UNESP]; Trevizan, Lilian Cristina; Padovani, Carlos Roberto [UNESP] (Instituto de Pesquisas Ambientais em Bacias Hidrograficas (IPABHi), 2019)
Several factors may contribute to changes in monitoring parameters of drinking water quality, especially climatic characteristics. Behavioral studies of these characteristics are relevant to the rational and sustainable use of water resources and better monitoring of the quality of water available for the population. To assess the association between water quality and climate, this research explored physical-chemical and microbiological characteristics considered important for the monitoring of water quality, analyzed in casual samples collected daily from the distribution system of a city, and considered monthly data of climatic characteristics from 2007 to 2011. The associations between these two sets of variables were assessed by the multivariate procedure of the canonical correlation analysis. The results indicate a positive correlation between the canonical variable formed by the linear combination of climatic variables and the canonical variable formed by the linear combination of water quality variables.
Análise canônica de fatores climáticos associados às características de qualidade da água potável de um município do Estado de São Paulo
Keywords: Canonical correlation; Climatic variables; Drinking water; Multivariate statistics